Characterization of histone lysine β‐hydroxybutyrylation in bovine tissues, cells, and cumulus–oocyte complexes. Issue 9 (8th July 2022) - Sangalli, Juliano R.; Nociti, Ricardo Perecin; del Collado, Maite; Sampaio, Rafael Vilar; da Silveira, Juliano C.; Perecin, Felipe; Smith, Lawrence Charles; Ross, Pablo J.; Meirelles, Flávio V.
Abstract: Besides their canonical roles as energy sources, short‐chain fatty acids act as metabolic regulators of gene expression through histone posttranslational modifications. Ketone body β‐hydroxybutyrate (BHB) causes a novel epigenetic modification, histone lysine β‐hydroxybutyrylation (Kbhb), which is associated with genes upregulated in starvation‐responsive metabolic pathways. Dairy cows increase BHB in early lactation, and the effects of this increase on cellular epigenomes are unknown. We searched for and identified that Kbhb is present in bovine tissues in vivo and confirmed that this epigenetic mark is responsive to BHB in bovine and human fibroblasts cultured in vitro in a dose‐dependent manner. Maturation of cumulus–oocyte complexes with high concentrations of BHB did not affect the competence to complete meiotic maturation or to develop until the blastocyst stage. BHB treatment strongly induced H3K9bhb in cumulus cells, but faintly in oocytes. RNA‐seq analysis in cumulus cells indicated that BHB treatment altered the expression of 345 genes. The downregulated genes were mainly involved in glycolysis and ribosome assembly pathways, while the upregulated genes were involved in mitochondrial metabolism and oocyte development. The genes and pathways altered by BHB will provide entry points to carry out functional experiments aiming to mitigate metabolic disorders and improve fertility in cattle.